Crossover and extension of hand-drawn map in heritage tourism: a case study - Zhe, Wang; Alli, Hassan; Md Yusoff, Irwan Syah (Jomard Publishing, 2024)
In the realm of thematic map development, hand-drawn maps tailored for tourism hold considerable significance. Nonetheless, their progress is impeded by inherent limitations and challenges, thereby constraining their potential advancement. Concurrently, the emergence and progression of computer and network technology have furnished a proficient platform for fostering interdisciplinary growth in the realm of hand-drawn cartography. The aim of this study is establishing a customized, culturally relevant, metaphorical and de-identified design framework for enhancing visualization in digital interactions, drawing upon the universal design principles inherent in traditional animation. A comprehensive depiction of the design workflow, along with intricate design particulars pertaining to each stage, was demonstrated through a case study centered on the hand-drawn style drawing and map design for Dahuaishu Ancestor Memorial Garden. By adopting such a design framework, the potential outcome entails a more user-friendly and captivating means of disseminating information within digital tourist maps of the same genre. This approach preserves the inherent merits of hand-drawn maps while simultaneously broadening their scope and capabilities.